One Market? Stocks, Futures, and Options During October 1987. - Kleidon, Allan W; Whaley, Robert E (Journal of Finance, 1992)
The authors provide new evidence regarding the degree of integration among markets for stocks, futures, and options prior to and during the October 1987 market crash. Where previous analyses have resulted in recommendations for the implementation of circuit breakers, the coordination of margin requirements across markets, and changes in regulatory jurisdiction, their analysis indicates that delinkage between markets during the crash was primarily caused by an antiquated mechanism for processing stock-market orders. The results suggest that market integration may be better served by efficient order execution than by further restricting markets.